The Value, Mode and Promotion Path of the Informatization of Veterinary Drug Production and Supervision. (January 2019) - Cheng, Guodong; Xing, Liwei; Cao, Shanshan; Han, Shuqing; Wu, Jianzhai; Zhang, Jianhua
Abstract: The veterinary drug industry is closely related to people's lives. The production and sale of counterfeit and inferior veterinary drugs, the illegal use of prohibited drugs, and the non-prescribed use of veterinary drugs have affected the prevention of animal epidemics and affected the quality of animal products, which will finally affect people's physical health. The intelligent management system for veterinary drug production and supervision (the system) can supervise the production, management and use of veterinary drug in an all-dimensional and multi-level manner in a wide range of fields. It has great research significance and broad application prospects. This paper mainly analyzes the significance of the system from three perspectives, studies its application prospects in different market entities, and analyzes the application and promotion of the system from two aspects.